Wastewater treatment performances of horizontal and vertical subsurface flow constructed wetland systems in tropical climate - Suwasa Kantawanichkul; Suparurk Wannasri (Songklanakarin Journal of Science and Technology (SJST), 2013)
The study was carried out in 4 concrete beds: two vertical subsurface flow beds (dimension of 1x1.4 x 0.6 m3) and twohorizontal subsurface flow beds (dimension of 0.6 x 2.3x 0.6 m3) planted with Cyperus alternifolius L. Under the averagewastewater temperature of 27°C, the hydraulic loading rates (HLR) were varied from 5 to 20 cm/d in order to obtain theoptimum operating conditions and compare the removal efficiency. The wastewater was intermittently fed into the verticalsubsurface flow beds (5 minutes on and 55 minutes off), and continuously into the horizontal subsurface flow beds. Themaximum removal efficiencies were found at the lowest hydraulic loading rate for both systems. The horizontal subsurfaceflow system had a higher removal rate than the vertical subsurface flow system in terms of COD (the removal rates at 5-20cm/d were 9.6-33.9 g/m2.d). The vertical subsurface flow system showed higher removal efficiency for TKN and NH4+-N, inevery hydraulic loading rate and the removal rates for TKN and NH4+-N were 0.4-1.1 g/m2.d, respectively. Furthermore, it wasfound that the uptake of N by plants in the horizontal flow system was higher than in the vertical flow system for everyhydraulic loading rate (HLR) but the loss of N via adsorption/denitrification was higher in the vertical flow system than inthe horizontal flow system, at 20 cm/d HLR. The removal rate constants in the horizontal subsurface flow system for COD andNH4+-N were 0.0166 and 0.0188 m/d and 0.0204 and 0.0287 m/d for the vertical subsurface flow system, respectively